PEMERIKSAAN HbsAg SISWA/SISWI SMA N 1 PUMU TANJUNG SAKTI KABUPATEN LAHAT UNTUK KUALITAS KESEHATAN REMAJA - Maria Nuraeni; Ian Kurniawan; Hotman Sinaga (Jurnal Abdimas Musi Charitas, 2018)
Health service is a primary need for our society. Health workers of Medical Laboratory Technology as a important role in public health needs through examination of human specimens including HBsAg. HBsAgused as a detection of hepatitis recorded by humans. Hepatitis B is a dangerous infectious disease while a problem in the world, especially Indonesia. Transmission of the hepatitis B virus is very easy and everyone has the potential to be infected, including high school students. Teenagers in high school do not understand the risks and health status that can be caused when infected with the Hepatitis B virus. Community service activities for students of SMAN 1 PUMU treatedHBsAg for 25 students with 1 student shows positive HBsAg results. This results indicate the potential for transmission of the Hepatitis B virus that can be transmitted if the the problem can’t be solved. Routine inspection programs need to do for early detection of Hepatitis B virus by collaborating with the stakeholders.